PENGARUH INFLASI DAN KURS TERHADAP HARGA SAHAM SELAMA PANDEMI PADA INDUSTRI KEUANGAN YANG TERDAFTAR DI BEI - Miftakul Janah; Anik Malikah; Hariri Hariri (Universitas Islam Malang, 2021)
The purpose of this study was to determine the effect of inflation and exchange rates on stock prices during the pandemic. The populations in this study were all financial banking industry companies listed on the Indonesia Stock Exchange in 2020. The sampling tecnique used purposive sampling and obtained as many as 44 companies, all of wich met the specified criteria. The data analysis method used in this research is multiple linear regression analysis. The results of this study indicate that the inflation and exchange rate variables simultaneously have a significant positive effect on stock prices during the pandemic. Partially, inflation has an effect on stock prices during the pandemic. The exchange rate variable partially effect stock prices during the pandemic.Keywords: inflation, exchange rate, stock price